The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.1007/s00438-015-1156-x
|View full text |Cite
|
Sign up to set email alerts
|

Identification, duplication, evolution and expression analyses of caleosins in Brassica plants and Arabidopsis subspecies

Abstract: Vous avez des questions? Nous pouvons vous aider. Pour communiquer directement avec un auteur, consultez la première page de la revue dans laquelle son article a été publié afin de trouver ses coordonnées. Si vous n'arrivez pas à les repérer, communiquez avec nous à PublicationsArchive-ArchivesPublications@nrc-cnrc.gc.ca. Questions? Contact the NRC Publications Archive team atPublicationsArchive-ArchivesPublications@nrc-cnrc.gc.ca. If you wish to email the authors directly, please see the first page of the pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 69 publications
1
26
0
Order By: Relevance
“…Motif 4 is a 30–50 residue domain present close to the N-terminus and is found in many CLO/PXG sequences throughout the Viridiplantae (and Fungi). This Motif is characteristic of the so-called H-caleosins (where H = high molecular weight), as previously reported from several labs [ 1 , 2 , 27 , 28 , 64 66 ]. We found that all Angiosperm genomes sequenced to date contain at least one copy each of the L- and H-caleosin sequences and although the evidence is less clear for the other Viridiplantae, it seems that most species also contain both isoforms.…”
Section: Resultssupporting
confidence: 80%
“…Motif 4 is a 30–50 residue domain present close to the N-terminus and is found in many CLO/PXG sequences throughout the Viridiplantae (and Fungi). This Motif is characteristic of the so-called H-caleosins (where H = high molecular weight), as previously reported from several labs [ 1 , 2 , 27 , 28 , 64 66 ]. We found that all Angiosperm genomes sequenced to date contain at least one copy each of the L- and H-caleosin sequences and although the evidence is less clear for the other Viridiplantae, it seems that most species also contain both isoforms.…”
Section: Resultssupporting
confidence: 80%
“…Our finding was consistent with previous evolutionary analyses. In addition, by comparing the gene family “intron–exon” number, length, distribution and other genetic structure, we can understand the genetic structure of the diversity and complexity of the reasons for the formation ( Shen et al., 2016 ). We found that in the OPT clade, 11 of 15 BrrOPTs contained 4–6 exons, similar to Arabidopsis , rice, Populus , and Vitis (4–7) ( Cao et al., 2011 ).…”
Section: Resultsmentioning
confidence: 99%
“…Gene duplication events are thought to have frequently occurred in organismal evolution ( Kent et al., 2003 , Mehan et al., 2004 ). Genome-wide duplication events, gene loss, and local rearrangements have created the present complexities of the genome ( Shen et al., 2016 ). In addition, we found that the turnip underwent broad-scale gene duplication events, OPT genes located chromosome duplicate region ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The lipid‐associated Ca 2+ binding ability also occurs in fungi and green algae (Naested et al ., 2000; Hanano et al ., 2006; Rahman et al ., 2018). Caleosin gene families have been annotated in castor bean and flax (Hyun et al ., 2013); wheat, barley, rye, rice and Brachypodium (Khalil et al ., 2014); Arabidopsis (Shen et al ., 2014); Brassicaceae (Shen et al ., 2016) and hazelnut (Lamberti et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%